The Utilization of “Jeda Nulis” Youtube Channel as Learning Media of Religious Tolerance for Virtual Communities - Mimi Sugiarti; Fauzi Fauzi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
Abstract: This research is oriented to analyze the use of Youtube as a learning media of religious tolerance for virtual communities. The focus of the research is on the